2021
DOI: 10.1108/jfc-10-2020-0213
|View full text |Cite
|
Sign up to set email alerts
|

The geographies of corruption in Nigeria: understanding the patterns and correlates

Abstract: Purpose Globally, corruption has been identified as a major problem. Even though corruption is widespread, it varies in magnitude, types and consequences. In Nigeria, corruption is endemic, and it is responsible for the many socioeconomic problems in the country. Hence, the study aims to determine the patterns and state level correlations of corruption in Nigeria. Design/methodology/approach Data for this study were sourced from the National Bureau of Statistics and other official sources and were analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Findings to objective one therefore showed that there appears to be some high level of corrupt practices in the country, Nigeria. In line with the findings of this study, Adeleke et al (2021) noted thus: In the world today, corruption is being identified as a terrible problem. Despite the fact that corruption is known to be widespread, it therefore varies in magnitude, also in types and consequences.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Findings to objective one therefore showed that there appears to be some high level of corrupt practices in the country, Nigeria. In line with the findings of this study, Adeleke et al (2021) noted thus: In the world today, corruption is being identified as a terrible problem. Despite the fact that corruption is known to be widespread, it therefore varies in magnitude, also in types and consequences.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…This is a task that the Nigerian library profession has taken on, and it is hoped that it will bear fruits. Corruption has been acknowledged as a big concern worldwide, according to Adeleke, Alabede, Osayomi, and Iyanda (2021). Despite the fact that corruption is pervasive, its extent, kinds, and repercussions vary.…”
Section: State Of Corruption In Nigeria Todaymentioning
confidence: 99%
“…The nation's public sector is accordingly the engine room of massive corruption in the country. The incidence of public sector corruption in the national system of Nigeria is simply indefinable and gargantuan (Ani Casimir, 2014;Okolo & Raymond, 2014;Ijewereme, 2015;Ugbomhe et al2018;Ogunlana, 2019;Kupoluyi et al2020;Onyekwere et al 2020;Adeleke et al 2021).…”
Section: The Consequences Of Disharmonymentioning
confidence: 99%